Jusepe de Ribera in the Kingdom of Valencia and the workshop of Juan Sariñena: the formation of an artist - DEBORAH FELLER (Boletín del Museo del Prado)
Jusepe de Ribera, known as lo Spagnoletto, was christened in 1591 in Játiva, Valencia. With documentation from his first twenty-one years solely consisting of his baptismal record, most writers assumed that his artistic formation began in Rome. Clues to his early training exist within the Valencian cultural and social milieus of the period, where the Archbishop of Valencia, Juan de Ribera, acquired works from Italy and the Low Countries, and the city’s official painter, the Aragonese Juan Sariñena (1545-1619), fulfilled commissions for the ecclesiastical and civic authorities. The article argues that the young Ribera learned to paint from Sariñena and that his master held the keys to Rome by virtue of his stay there and his connections with the Aragonese national church in that city.